MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SEBAGAI INSTRUMEN INTERNALISASI NILAI KEISLAMAN DI MTsN 4 PASAMAN BARAT - Yuharnis, Yuharnis; Sari, Fitria; Laili, Wahyu; Syakban, Ismail (STKIP Pesisir Selatan, 2025)
Objective : This study aims to analyze the role of Islamic Religious Education learning media as an instrument for internalizing Islamic values at MTsN 4 Pasaman Barat. Methods: This research employed a qualitative descriptive approach. Data were collected through classroom observations, in-depth interviews with Islamic Religious Education teachers and students, and documentation studies. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. Results: The findings show that various learning media such as audio-visual media, digital presentations, Islamic educational videos, and contextual teaching aids significantly support the internalization of Islamic values, including faith (iman), worship (‘ibadah), and morals (akhlaq). The use of appropriate media increases students’ engagement, understanding, and practice of Islamic values in daily life. Novelty: This study highlights the integrative function of learning media not only as instructional tools but also as value-internalization instruments within Islamic education at the madrasah level.